The People's Health - Hastings, Somerville, 1878-1967 (London : The Labour Party)
1932-07 1932 1930s 24 pages (2) Poor Law. It must be the object of legislation to get rid of the Poor Law Medical Service as rapidly as possible and merge it with the other services provided for those not destitute. As a first step no more part-time District Medical Officers under the Poor Law should be appointed. These, it will be remembered, are general practitioners who provide domicilary [domiciliary] and other treatment for patients who are technically paupers. Where the position of District Medical Officer becomes vacant, it should be filled either by combining districts or by the appointment of a full-time medical officer attached to the Municipal Hospital, or in cases where appropriation under the Local Government Act of 1929 has not taken place, to the Infirmary. At the same time the supervision of all the district medical work under the Poor Law which is now entrusted to the Public Assistance Committees, should be transferred to Public Health Committees and as soon as the General State Service free and open to all, has been established as described above, it will only be necessary for the Local Public Assistance Committee to register those persons in receipt of public assistance who are not already registered for a Home doctor to be allotted to them. In this way, the poor law medical service will be absorbed completely in the General State Service. (3) Hospitals. A very slight amendment of the present law will suffice to achieve what was clearly the intention of the framers of the Local Government Act, 1929, viz., the transference of all Poor Law Infirmaries to the Public Health Committees and their development as Municipal Hospitals under Section 131 of the Public Health Act, 1875. Pressure should then be made on the Local Authorities by the Ministry of Health to induce them to develop these Municipal hospitals on the best lines possible, and to withdraw from them all taint of the Poor Law by insisting that any payments made by patients should be determined and collected entirely apart from machinery of Public Assistance. It is possible at the present time for any charitably minded person to found and develop a voluntary hospital for the treatment of any kind of disease without consideration of the existing facilities for treatment or the needs of the district. This is most undesirable and it is definitely in the public interest that voluntary hospitals should be registered or licensed just as nursing homes, public houses, and theatres, are. In some ways it is even more necessary as the good work carried out in most voluntary hospitals may induce patients to put their trust in institutions that are not worthy of it. Therefore, legislation should be passed to ensure that all voluntary hospitals 18 292C/155/1/1